Stabilisasi Tanah Lempung Plastisitas Tinggi Dan Sedang Menggunakan Kapur - Z, Mauliza A.; A, Nugroho S.; G, Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Clay is soil with grain diameter <0.075 mm. Clay has poor properties in bearing capacity in terms of compressibility, permeability, and plasticity. One effort to improve soil properties is soil stabilization. Effective clay stabilization is by adding certain chemicals material such as lime. Lime is calcium oxide (CaO) made from carbonate stones that are heated at very high temperatures. The purpose of this study was to determine the effect of lime addition on clay characteristics. The variation of lime used in this study is 0%, 3%, 5%, 7% and 10%. The results showed that lime effectively reduced dry plasticity and density. The plasticity value is reduced by up to 50% from the original clay soil (CL) compared to Minas clay which is reduced by 7%. MDD (Maximum Dry Density) decreased by 10% in the Minas clay and OMC (Optimum Moisture Content) increased by 32% in the Palas clay. Keywords :Clay, Density, Lime, Plasticity, Stabilization.